Narratologia Lévi-Straussa – lektury polemiczne - Graf, Paweł (My University, 2011)
The article addresses the origins of narratology – the methodology whose forerunner was Vladimir Propp. The author emphasizes polemic nature of Lévi- -Strauss’ critical analysis of Morphology of the Folk Tale by Propp. Moreover, he criticizes Lévi-Strauss’ approach to myth indicating that his model of structural analysis of myth, despite its strengths, has also basic and important defects. In conclusion, the author discusses narratology “after Lévi-Strauss”.
Lévi-Strauss’s Narratology – The Polemic Readings
Tekst jest teoretycznoliteracką analizą sporu, który wynikł między Claudem Lévi-Straussem i Władimirem Propem (na kanwie "Morfologii bajki), który to spór ufundował europejską narratologię.
Keywords: Władimir Propp; narratology,; Claude Lévi-Strauss; narratologia; morfologia bajki; morfology of the folk